Simple Additive Weighting on The Selection of Candidate Students in The Job Skills Training Program - R Rayendra (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The Job Skills Training Program (JST) is an education and training service program that is oriented towards the development of job skills in accordance with industrial needs, given to students so that they have competence in certain skill areas as evidenced by a certificate of competence to work and be absorbed in the business and industry. Course institutions that receive assistance from this program often experience problems in the selection of potential candidates because the number of applicants is large enough to meet the same criteria while students are limited. The Simple Additive Weighting (SAW) method is one of the decision support methods used in this study to obtain alternative candidate students who match the criteria. From the results of calculations using the SAW Method, it is concluded that the SAW Method can be used to support decision making in the selection of JST Program candidates that produce the highest-ranking scores.